Peningkatan pemahaman perilaku swamedikasi dengan metode Theory Planned Behaviour dalam promosi kesehatan - Ressy Elsis GS; Ketrin Sadna M; Dheilla Fadilla; Stefanus Dicky R; I Gusti Ayu Dyah (Jurnal Pengabdian Harapan Ibu (JPHI), 2022)
Swamedikasi is Self-medication can be a health problem because of limited knowledge about drugs, so it will affect a person behavior. Improper implementation of self-medication will cause other health problem. This health promotion aims so that teachers can understand the right self-medication such as drug selection, how to use the drug, and the appropriate dose. This counseling method is in the form of direct interviews with Theory Planned Behaviour (TPB) method. Participants in this program are all 33 female teachers of SMKS Fania Salsabila Jambi city, totaling 33 people. But, in this activity there were only 20 respondents, because 13 of them were male teachers. The result was that 20 participants showed that 100% of participants had done self-medication to deal with complaints they felt. The results of the benefits of self-medication for all participants answered that they were more efficient, while the disadvantages of self-medication were 80% of the participants admitted that they were wrong in setting the dose and 20% of the participants said that “in some conditions the drugs used were not in accordance with the complaints”. In conclusion Theory Planned Behaviour (TPB) id needed because it is important to know individual perceptions about a population in a particular social environment that supports or opposes behavior carried.